A Discrete Predator-prey Model with Allee and Refuge Effect (European Journal of Pure and Applied Mathematics, 2023)
We consider a predator-prey model, where some prey are completely free from predation within a temporal or spacial refuge and the predator population is subject to Allee effect. We study the effect of the presence of refuge and Allee effect on the stability and bifurcation of the system. We investigate the existence and stability of the model as well as the stability region. We also obtain the invariant manifolds of the system.
Keywords: center manifold; Allee Effect; Refuge Effect